Ḥifẓ Al-Lisān as Maqāṣid Al-Sharī'ah Al-Ḍarūriyyah (Its Importance and Relevance in the Contemporary Era) - Hamim, Khairul (Islamic Family Law Department, Sharia and Law Faculty, Universitas Islam Negeri Ar-Raniry, 2021)
This study examines the urgency and relevance of ḥifẓ al-lisān to be included as a part of al-ḍharūriyyāt from the five main points (al-ḍharūriyyāt al-khams) which have to be maintained and is the main level in the study of maqāṣid al-sharī'ah. The transformation of ḥifẓ al-lisān as maqāṣid al-sharī'ah al-ḍarūriyyah has a pivotal role in today's contemporary era. This study only focus on two important aspects such as how ḥifẓ al-lisān is being used as an important part of maqāṣid al-sharī'ah in the al-ḍharūriyyāt and to what extent the urgency and relevance of ḥifẓ al-lisān as maqāṣid al-sharī'ah in the contemporary era. This study employed inductive analysis as a method of analysis. The sources are books related to maqāṣid al-sharī'ah written by Islamic jurists. The results of this study reveal that ḥifẓ al-lisān is suitable and urgent to be included as a part of maqāṣid al-ḍarūriyyah based on the arguments of aqli and naqli as well as phenomena that occur in the today’s contemporary era. Ḥifẓ al-lisān is necessary to do in terms of harmonizing life of society, nation and state. However, by ignoring ḥifẓ al-lisān has an impact on the emergence of negative attitudes such as provocation, slander, sarcasm, racism, spreading hoax news, hate speech and others. This negative attitude must be stopped because it certainly creates mafsadat for the community, nation and state.